Magnetic Field Mapping Around Individual Magnetic Nanoparticle Agglomerates Using Nitrogen‐Vacancy Centers in Diamond. (16th July 2021) - Camarneiro, Filipe; Bocquel, Juanita; Gallo, Juan; Bañobre‐López, Manuel; Berg‐Sørensen, Kirstine; Andersen, Ulrik Lund; Huck, Alexander; Nieder, Jana B.
Abstract: A modified diamond–photonics based metrology is proposed to explore the magnetic fields created by agglomerates of magnetic nanoparticles (MNPs). MNPs are promising for environmental and medical applications; those proposed for cancer magnetic hyperthermia treatments are small superparamagnetic <20 nm iron oxide particles. Inside cells, they assemble in larger MNP agglomerates, reaching cross‐sections of several micrometers. Here, these conditions are reproduced and MNP agglomerates immobilized. Optically detected magnetic resonance (ODMR) signals recorded without a bias field in a confocal microscope and scanning across a homogenous shallow layer of fluorescent nitrogen‐vacancy centers in a bulk diamond sample placed in direct contact with the MNP agglomerates are used to determine magnetic fields with a spatial resolution of 500 nm in a lateral direction. This spatial resolution allows determining magnetic field maps around individual MNP agglomerates, for which magnetic fields with strengths ranging from 0.03 mT to maximal 1.2 mT in the direct vicinity of the agglomerates and with detectable fields up to 5 µm away from the agglomerates, are determined. Based on the findings, a pathway to non‐invasively study the micro/nano topology of MNP agglomerates is proposed. Abstract : Diamond photonics are proposed for magnetic field characterization of magnetic nanoparticles agglomerates, with sizes similar to agglomerates found upon cellular uptake inside cells. Optically detected magnetic resonance signals recorded without a bias field on the color center‐implanted diamond reflect magnetic fields between 1.2 mT in the direct vicinity and 0.03 mT at distances of 5 um away from the agglomerate surface.